The Biodiversity and Distribution of Abyssal Benthic Foraminifera and Their Possible Ecological Roles: A Synthesis Across the Clarion-Clipperton Zone - Gooday, Andrew J.; Lejzerowicz, Franck; Goineau, Aurélie; Holzmann, Maria; Kamenskaya, Olga; Kitazato, Hiroshi; Lim, Swee-Cheng; Pawlowski, Jan; Radziejewska, Teresa; Stachowska, Zofia; Wawrzyniak-Wydrowska, Brygida (Frontiers in Marine Science, 2021)
Benthic foraminiferal research in the North Pacific has a long history, with works published over a century ago providing important information about the taxonomy and distribution of morphospecies. These studies focused mainly on areas outside the Clarion-Clipperton Zone (CCZ). Our knowledge of foraminiferal faunas within the CCZ originates largely from recent baseline investigations related to likely future seabed mining of the polymetallic nodule deposits. These have revealed highly diverse assemblages of sediment-dwelling morphospecies among the meiofauna and macrofauna, as well as megafaunal xenophyophores and nodule-attached fauna. Morphological analyses have been complemented by metabarcoding studies that yielded even higher numbers of molecular species (Operational Taxonomic Units - OTUs). Monothalamids, the vast majority undescribed, constitute a substantial proportion of both morphological and molecular datasets, with multichambered agglutinated and calcareous foraminifera being less common. Their importance in this abyssal (>4,000 m depth) habitat likely reflects food limitation combined with carbonate dissolution close to and below the carbonate compensation depth. Literature records, supported in a few cases by genetic data, suggest that many morphospecies found in the CCZ have wide geographical distributions across the Pacific abyss and in other oceans. At smaller spatial scales (several 100s of kilometers) there is a general uniformity in assemblage composition. Nevertheless, many morphospecies are too rare to conclude anything about their geographical distributions. Similarly, the part played by benthic foraminifera in CCZ ecosystems is largely a matter of speculation, although their abundance across different size classes suggests that it is significant. Meiofauna-sized taxa that consume freshly-deposited organic detritus may be important in carbon cycling, particularly at the shallower, more eutrophic eastern end of the CCZ. Megafaunal xenophyophores can provide habitat structure for other organisms, potentially enhancing benthic biodiversity. Foraminifera of all sizes could be among the earliest recolonisers of disturbed or redeposited sediments. Their potential contributions in terms of both ecology and biodiversity make these protists significant members of benthic communities in the CCZ.